Influência do uso da terra na qualidade da água em bacias hidrográficas com usos distintos, em Jataí-GO e Canápolis-MG - Lopes, Simone Marques Faria (2016)
We start from the hypothesis that the land use model existent in Paraíso-GO creek and Cerrado/Cadunga-MG stream river basins has been providing significant changes in the water quality of these streams, which receive sediments and nutrients from natural and anthropic factors. In this sense, the general aim of this research is to diagnose the water quality in relation to the model of land use and physical characteristics of the basins. The methods used followed the procedures of the American Public Health Association (APHA), CONAMA legislation nº 357/2005 (surface water) and ordinance of the Ministry of Health 2914/2011 (drinking water). When comparing the geological aspects of the two basins, it was verified that they are differentiated by the presence of the unconsolidated sands in the upper part of the Paraíso creek. Regarding the soils, both are distinguished by the presence of Cambisols in the Paraíso creek, and are similar in relation to the presence of soils with hydromorphic characteristics. Studies of land use between 2005 and 2015 demonstrated the gradual disappearance of the Cerrado biome, mainly in the Cerrado/Cadunga river basin. The watershed region of the Paraíso creek presented greater erosive potential in formation areas of the Vale do Rio do Peixe, as well as the Cerrado/Cadunga stream. Heavy metals contents in those soils identified at different sampling points reveal occasional contamination, mainly related to land use. In general, the sediment results of Cerrado/Cadunga stream showed that the distribution of elements has as main contribution the urban area and the discharge of urban and industrial effluents in the drainage network, and for the soils, agro-pastoral activities. For the Paraíso creek basin, the greatest influence was linked to agricultural activities, especially sugarcane. Out of the heavy metals found in both basins analyzed, what demands greater attention, both in sediments and in soils, is cadmium. Regarding the framing of water bodies, it was verified that the Paraíso creek and the Cerrado/Cadunga stream were included in all the sampling campaigns in classes III and IV of CONAMA Resolution nº 357/2005, since the variables Phosphorus, Cadmium and Cupper showed higher values than those established by the abovementioned Resolution. According to the classification of the water bodies of both basins, they can be used for human supply, after conventional or advanced treatment, to irrigation, amateur fishing, recreation and also animal watering. In this sense, it was concluded that the land use presented in both basins, due to the use of agrochemicals, poses significant risks to water quality, as well as the release of domestic and industrial effluents, since the basins evaluated presented changes in the same parameters evaluated.